An aggregate taxonomy for crowdsourcing platforms, their characteristics, and intents - Fernando Ressetti Pinheiro Marques Vianna; Alexandre Reis Graeml; Jurandir Peinado (BAR: Brazilian Administration Review, 2022)
This article intends to categorize different classifications used in the literature to distinguish among crowdsourcing platform types, based on their characteristics and intents. This is performed by means of a systematic literature review. The search for texts that combined the terms ‘crowdsourcing’ and ‘taxonomy,’ on the Google Scholar platform, resulted in 61 potential articles to be included in the corpus of the research, which were reduced to 13, after applying additional filtering. The study shows that taxonomies and classifications of platforms differ from author to author, each one of them adopting his/her own criteria and terminology. The 65 different crowdsourcing classifications that were found in the reviewed studies were reorganized in 16 groups, based on their characteristics. We believe that the current work contributes to the standardization of terminology and categorizations adopted in the literature and, therefore, to a better understanding of the crowdsourcing phenomenon.